On the Logicality of Primitive Thinking - Gendrolis, Edmundas (Problemos, 1975)
In his review article, E. Gendrolis distinguishes three groups of theories: in the first group, ancient hominids are considered exclusively as biological creatures showing no capacity for thinking; in the second, he argues in favour of the image and not concept type of thinking by homo sapiens; in the third, conceptual thinking is being contributed already to ancient hominids.